Practice of Implementing Ecopreneur Values in MSMEs in Special Region of Yogyakarta - Riani, Lilia Pacsa; Mulyani, Endang; Manik, Yuni Mariani; Supriyanto; Sumarsih, Sri (Sinergi International Journal of Management and Business, 2025)
The growing urgency of sustainability challenges demands transformative entrepreneurial practices that integrate environmental responsibility into business operations. Study explores ecopreneurial values, drivers, and barriers in Yogyakarta culinary MSMEs. This study offers new empirical evidence that business scale, rather than age or capital, is the key determinant of sustainability integration among MSMEs. It further reveals that cognitive constraints—such as limited knowledge, awareness, and green literacy—exert a stronger influence than financial limitations in shaping ecopreneurial decision-making. This study employed a quantitative, cross-sectional survey of 100 culinary MSMEs in the Special Region of Yogyakarta. Data were analyzed using descriptive statistics, one-way ANOVA, post-hoc tests, and ANCOVA to assess the influence of MSME classification while controlling for business age and capital. Findings reveal significant differences across business classifications in adopting ecopreneurship values (F = 56.622; p < 0.001; η² = 0.539), with medium enterprises demonstrating the strongest implementation. The dominant barriers are lack of information (30%) and limited awareness (25%), while key drivers are market opportunity (28%) and autonomy motivation (25%). Ecopreneurship advancement among MSMEs is primarily capability-driven and shaped by motivational and informational factors rather than financial strength or experience. Policy interventions should therefore adopt classification-based strategies, focusing on green literacy, market access enhancement, and collaborative ecosystem development, especially for micro and small enterprises. The key implication is these findings suggest that national and regional policies should prioritize knowledge-based capacity building and ecosystem collaboration rather than merely providing financial incentives, ensuring a more inclusive and enduring green transformation of MSMEs.